Da'wah Communication and Social Concern - Suprapto, Budi; Zainuddin, Datin Hasmah (Selected Topics in Humanities and Social Sciences Vol. 8, 2021)
History has recorded that Islamic da’wah implemented by the early generation of Muslims, is a monumental example from the transformation process of very impressive value. It reached social, political, economic, cultural areas and the systems of Muslim societies’ belief. Al-Ghazali in Ihya ‘Ulumu al-Din wrote, indeed ‘amar makruf nahi munkar’ is the most important milestone of the great religions, and become the basis for the coming of the prophet. The result of the analyses show that the message of da'wah is not always capable of fostering social concern behaviours. In other words, the contents of da’wah message should not be only textual but also must be contextual to the social, cultural, economic, and political realities developed in society. In this way, da’wah activity could give the answer on the problems that experienced by the society.